Experimental Study on Distributed Measurement of Internal Pressure in Lithium-Ion Batteries Using Thin-Film Sensors - Qingyun Liu; Xiuwu Wang; Jiangong Zhu; Guiwen Jiang; Xuezhe Wei; Haifeng Dai (World Electric Vehicle Journal)
With the rapid development of electric vehicles, the safety and reliability of lithium-ion batteries (LIBs), as their core energy storage units, have become increasingly prominent. The variation in internal battery pressure is closely related to critical issues such as thermal runaway, mechanical deformation, and lifespan degradation. The non-uniform distribution of internal pressure may trigger localized hot spots or even thermal runaway, posing significant threats to vehicle safety. However, traditional external monitoring methods struggle to accurately reflect internal pressure data, and single-point external pressure measurements fail to capture the true internal state of the battery, particularly within battery modules. This limitation hinders efficient battery management. Addressing the application needs of electric vehicle power batteries, this study integrates thin-film pressure sensors into LIBs through the integrated functional electrode (IFE), enabling distributed in situ monitoring of internal pressure during long-term cycling. Compared to non-implanted benchmark batteries, this design does not compromise electrochemical performance. By analyzing the pressure distribution and evolution data during long-term cycling, the study reveals the dynamic patterns of internal pressure changes in LIBs, offering new solutions for safety warnings and performance optimization of electric vehicle power batteries. This research provides an innovative approach for the internal state monitoring of power batteries, significantly enhancing the safety and reliability of electric vehicle battery systems.